Hubungan Persepsi Keterlibatan Ayah dalam Pengasuhan Anak Dengan Perilaku Moral Anak di Sekolah - Irma Safitri; Ade Dafa Salsabila; Siti Nginayah (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2021)
The moral behavior of children at school is one aspect of child development that needs to be considered in its development. One of the things that affect the moral behavior of children is parenting, namely the involvement of the father in parenting. Moral behavior is behavior that conforms to the moral code of a social group. Moral behavior in this study is the moral behavior of children at school, namely behavior that is in accordance with school rules, consisting of discipline, responsibility and courtesy. Father involvement in child care is how a father is involved in child care, consisting of being involved and emotionally attached to children, being involved in handling children's problems, commitment to giving orders and control over children, and providing examples of behavior in children. Based on the Product Moment correlation analysis, the results show that there is a significant relationship between father's involvement in child care and children's moral behavior at school. This can be seen from the correlation value of (rcount) of 0.599, which is greater than the significance level of 5% or (0.05) and the correlation value is positive.